ETHNOMATHEMATICS IN BANYUWANGI CULTURE FOR MATHEMATICS EDUCATION: EVIDENCE FROM A SYSTEMATIC LITERATURE REVIEW: Jawa Timur, Indonesia - Putri Ekasari, Siti Nabila; Nia Wahyu Damayanti (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to examine the potential of Banyuwangi culture as a resource for mat matics learning through a Systematic Literature Review (SLR) approach. The review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol to ensure a systematic and transparent literature selection process. Literature searches were carried out in the Google Scholar and Garuda databases for publications published between 2020 and 2025 using keywords related to ethnomathematics, Banyuwangi culture, and mathematics learning. The inclusion criteria consisted of articles discussing elements of Banyuwangi culture containing mathematical concepts or their implementation in mathematics learning, while publications that were not relevant to the research context or were not available in full text were excluded. The selection process included identification, screening of titles and abstracts, full-text eligibility assessment, and quality appraisal of the studies. Based on this process, 13 articles met the criteria and were included in the analysis. The synthesis results indicate that various elements of Banyuwangi culture, such as Osing batik motifs, traditional dances, traditional house architecture, weaving crafts, and community traditions, contain mathematical concepts including geometry, symmetry, similarity, number patterns, and measurement. The integration of these cultural elements in mathematics learning contributes to improvements in cognitive learning outcomes, numeracy and literacy skills, learning motivation, and students’ character development, each measured using different instruments. These findings indicate that Banyuwangi culture has strong potential as a contextual and culturally responsive resource for mathematics learning. Keywords: Ethnomathematics; Banyuwangi Culture; Learning Resources; Systematic Literature Review; Mathematics Learning